The Role of Foreign Harem and Queen In The Fall of The Ottoman Empire: A Siyasah Shar'iyyah Perspective - Rahmi, Rahmi; Ilhamni, Ilhamni; Meirison, Meirison; Humairoh, Roza (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2025)
The article from this research aims to explain the role of women and foreign women in the Ottoman government, which had positive and negative impacts on the Empire. At first, the role of women was not very prominent in government. However, women behind the scenes produced strong leaders who could increase the age of this Empire and experience a period of glory starting with the reign of Usman I. In Sultan Suleiman the Magnificent, the role of foreign women and enslaved people became more prominent. Repeated attempts by women in power at the Ottoman court to take different roles profoundly affected the state's internal structure in the long term, especially in foreign diplomacy. The mothers and wives of the sultans could build entities within the state, and they had supporters from ministries and the army. It is worth noting that "one of the most important factors in halting the progress, and even setting back the Ottoman Empire, was the interference of the sultan's foreign wives and mothers for almost a century in state affairs." Court ladies strongly influenced the sultans, especially in the 17th Century, when the state was sometimes under their rule. The welfare of Muslims was disrupted in areas of Russia, Eastern Europe, Malaysia, and Indonesia.